Combining nudges and boosts to increase precautionary saving: A large-scale field experiment - Shane Timmons; Deirdre A. Robertson; Pete Lunn (The Economic and Social Research Institute (ESRI), 2022)
Many households lack savings to cushion them from financial shocks. While behavioural economics offers insights into why some households who want to save may fail to do so, successful behavioural interventions to increase precautionary saving are elusive. We incorporated multiple evidence-based "nudges" and "boosts" into a savings account application form at a major commercial bank and designed an electronic marketing communication to explain cumulative risk based on a scalable boost. In a pre-registered randomised controlled trial, these interventions increased saving account uptake by 25-40%. Moreover, some effects were concentrated among low-income households.
Keywords: 330; Vorsichtssparen; Nudge; Sparförderung; Feldforschung; Experiment; Irland